Physicochemical Salt Solution Parameters Limit the Survival of Planococcus halocryophilus in Martian Cryobrines - Waajen, Annemiek C.; Heinz, Jacob; Airo, Alessandro; Schulze-Makuch, Dirk (Frontiers in Microbiology, 2020)
Microorganisms living in sub-zero environments can benefit from the presence of dissolved salts, as they significantly increase the temperature range of liquid water by lowering the freezing point. However, high concentrations of salts can reduce microbial growth and survival, while evoking a physiological stress response. It remains poorly understood how the physicochemical parameters of brines (e.g. water activity, ionic strength, solubility, hydration shell strength between the ions and the surrounding water molecules) influence the survival of microorganisms. We used the cryo- and halotolerant bacterial strain Planococcus halocryophilus as a model organism to evaluate the degree of stress different types of salts assert. Cells were incubated in liquid media at -15°C containing single salts at eutectic concentrations for nine salts (CaCl2, LiCl, LiI, MgBr2, MgCl2, NaBr, NaCl, NaClO4, NaI). Four of these salts (LiCl, LiI, MgBr2, NaClO4) were also investigated at concentrations with a low water activity (0.635) and, separately, with a high ionic strength (8 mol/L). Water activity of all solutions was measured at -15°C. This is the first time that water activity has been measured for such a large number of liquid salt solutions at constant sub-zero temperatures (-15°C). CFU counts show correlations between a decrease in survival of P. halocryophilus either with an increase in salt concentration, molecular weight of the anion, anion radius, with a decrease in water activity, or the anions´ hydration shell strength. The survival of P. halocryophilus did not show a significant correlation with the ionic strength, the molecular weight of the cation, the hydrated and unhydrated cation and hydrated anion radius, and the cations’ hydration bond length. These findings improve our understanding of the limitations of microbial life in saline environments, which provides a basis for better evaluating the habitability of extraterrestrial analog environments such as Martian cryobrines.